GENOTYPING AND IDENTIFICATION OF SIX DATE PALM (PHOENIX DACTYLIFERA L.) CULTIVARSOF THE GAZA STRIP BY RANDOM AMPLIFICATION OF POLYMORPHIC DNA - Kichaoui , A. El; Zayed, M. A. Abu; Ayesh, B. M. (Emirates Journal of Food and Agriculture)
Date palm (Phoenix dactylifera L.) is one of the major fruit crops in the Gaza Strip. The main cultivars are Hayani, Bentaisha, Barhi, Zahedi, Ameri and Halawy. Because of the difficulty associated with morphological identification of date palm cultivars, development of cultivar specific genetic markers have been extensively studied. The purpose of this study was to optimize and apply a reliable molecular marker protocol for genotyping and identification of these cultivars. Random amplification of polymorphic DNA (RAPD) was used to study the genetic diversity among the six cultivars using 42 primers. Genetic similarity matrices were constructed for the six cultivars using the Nei and Li formula and clustered with the UPGMA to determine the relationships between the six cultivars. Nine primers were informative and reproducible, and gave a number of polymorphic bands (on average, 7.2 bands per primer). The overall level of polymorphism was 49%. Genetic similarity among the six cultivars ranged from 76.3 to 93.5%. Some primers gave reproducible cultivar-specific bands that may be reliable to identify that cultivar. Our study introduces for the first time a molecular marker approach, capable of distinguishing and studying the genetic diversity among the six date palm cultivars in the Gaza Strip.